2020
DOI: 10.3390/w12030823
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow Decline in the Yellow River along with Socioeconomic Development: Past and Future

Abstract: Human society and ecosystems worldwide are increasinAagly threatened by water shortages. Despite numerous studies of climatic impacts on water availability, little is known about the influences of socioeconomic development on streamflow and water sustainability. Here, we show that the streamflow from the Yellow River to the sea has decreased by more than 80% in total over the last 60 years due to increased water consumption by agricultural, industrial and urban developments (76% of the streamflow decrease, sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
(98 reference statements)
0
13
0
Order By: Relevance
“…We further tested the significance of the average annual river discharge and sediment load due to the dam regulations in the two deltas (Figure 4a-d). The results showed that As for the Yellow River Delta, the river discharge and sediment load decreased gradually from 1950 to 2017 [41,66,67]. Corresponding to the construction of the four major dams (i.e., the Sanmenxia, Liujiaxia, Longyangxia, and Xiaolangdi Dams) [5], we divided the study period into five phases: phase i (1950-1960), phase ii (1961-1968), phase iii (1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985), phase iv (1986-1999) and phase v (2000-2017) (we use lowercase letters to make a distinction from the different phases of the Volta River Delta, Figure 3b).…”
Section: Hydrological Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…We further tested the significance of the average annual river discharge and sediment load due to the dam regulations in the two deltas (Figure 4a-d). The results showed that As for the Yellow River Delta, the river discharge and sediment load decreased gradually from 1950 to 2017 [41,66,67]. Corresponding to the construction of the four major dams (i.e., the Sanmenxia, Liujiaxia, Longyangxia, and Xiaolangdi Dams) [5], we divided the study period into five phases: phase i (1950-1960), phase ii (1961-1968), phase iii (1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985), phase iv (1986-1999) and phase v (2000-2017) (we use lowercase letters to make a distinction from the different phases of the Volta River Delta, Figure 3b).…”
Section: Hydrological Alterationmentioning
confidence: 99%
“…[5,77]. Notably, the erosion of the subaqueous delta and adjacent shelf zone may provide a sediment source to partly compensate for the decreasing fluvial sediment input, which could help to stabilize the shoreline and subaerial delta [66]. However, the coast of the Volta River Delta is bounded by a narrow shelf, which is characterized by a fairly uniform, moderately steep slope of between 1:120 and 1:150 up to −15 m [25,83,84], whereas the subaqueous slope of the Yellow River Delta is relatively low, ranging from 1:900 to 1:2500 [48].…”
Section: Conceptual Model Showing the Processes Of Dam-influenced Delta Evolutionmentioning
confidence: 99%
“…Due to more reservoir storage (Yang et al, 2020) and coarsening of surface sediment of lower riverbed (Fig. 4b), the functional degradation of the WSRS in both water-regulation and sediment-regulation periods has led to visible decrease in both water discharge and sediment load to the sea during the period of the WSRS (Fig.…”
Section: Sustainability Of the Wsrsmentioning
confidence: 99%
“…Due to more reservoir storage (Yang et al, 2020) and coarsening of surface sediment of lower riverbed (Figure 4b), the functional degradation of the WSRS in both water‐regulation and sediment‐regulation periods has led to visible decrease in both water discharge and sediment load to the sea during the period of the WSRS (Figures 2c and 4c). Since 2006, when the downstream riverbed erosion efficiency began to decrease (Wang et al, 2017), the sand load has dramatically declined (Figure 4c, with exception for 2010 when three WSRS events were unprecedentedly operated).…”
Section: Sustainability Of the Wsrsmentioning
confidence: 99%
“…The streamflow is almost entirely consumed in the oasis, and then disappears in the dry plains [8,9]. Streamflow consumption is a complex system dependent on natural conditions and human-induced effects [9][10][11][12][13]. Hu et al (2021) quantified the contributions of climatic and human activity factors to runoff variation by the elasticity coefficients in the Amu Darya River Basin [10].…”
Section: Introductionmentioning
confidence: 99%